2019
DOI: 10.1051/itmconf/20193012006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the dynamics of microwave pyrolysis of peat

Abstract: The work is devoted to the study of the effect of high-power microwave radiation on sphagnum peat. To implement the microwave pyrolysis process, a laboratory unit based on a coaxial resonator has been created. An industrial magnetron with a frequency of 2.45 GHz was used as a source of microwave radiation. Samples of gas, liquid and solid phases were obtained and analyzed. Studies of soft microwave pyrolysis in conditions of constant removal of gaseous reaction products were carried out. A comparative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…The mass content of carbon, hydrogen, and nitrogen in the solid product obtained as a result of elemental analysis of the solid product after microwave pyrolysis is shown in Figure 6 without sulfur (it was lower than limit of detection-0.3%). According to the results of previous studies [38,39] and the model experiments carried out, the applied conditions provide deep processing with a high yield of useful products due to longer thermal degradation of the feedstock and the optimal reaction rate in the operating reactor chamber. It is important to note that such a deep processing regime was obtained in a very wide range of loading volumes and was accompanied by intensive release of oily and gaseous fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass content of carbon, hydrogen, and nitrogen in the solid product obtained as a result of elemental analysis of the solid product after microwave pyrolysis is shown in Figure 6 without sulfur (it was lower than limit of detection-0.3%). According to the results of previous studies [38,39] and the model experiments carried out, the applied conditions provide deep processing with a high yield of useful products due to longer thermal degradation of the feedstock and the optimal reaction rate in the operating reactor chamber. It is important to note that such a deep processing regime was obtained in a very wide range of loading volumes and was accompanied by intensive release of oily and gaseous fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, simulations demonstrated that by optimizing the size and configuration of the reactor and the waveguide transmission line, it was possible to achieve sufficiently high uniformity of the distribution of the electromagnetic field inside the operating chamber. Thus, the problem of uneven heating, which is present in various studies (see, for example [38,39]), can be solved.…”
Section: Waveguide Bending Anglementioning
confidence: 99%